FUNGSI PENGAWASAN CAMAT DALAM MENINGKATKAN DISIPLIN KERJA PEGAWAI DI KECAMATAN TORIBULU KABUPATEN PARIGI MOUTONG - Moh ahdi; Suasa; Sasterio (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the Subdistrict Supervision Function in Improving Employee Work Discipline at the Toribulu Subdistrict Office, Parigi Moutong Regency. This study used a method with descriptive qualitative data. The research location is located at the Toribulu District Office, Parigi Moutong Regency. The data obtained in this study are from observations, interviews, and documentation. The results of this study show that the Subdistrict Supervision Function in Improving Employee Work Discipline at the Toribulu Subdistrict Office, Parigi Moutong Regency has not been maximized. among others: From the aspect of thickening the sense of employee responsibility, it has not been maximally seen, this is because there are some employees who neglect their duties and responsibilities as employees where they should be in the place when working hours take place the opposite happens. Educating Employees has not been fully implemented because there are still some employees who do not understand their duties and functions. Preventing Distortion, not implemented properly, this is because in every activity involving the sub-district, the sub-district itself does not participate in supervising the course of activities. Correcting Mistakes and Misappropriations, does not work as it should because there are still some employees who make irregularities and mistakes including errors in work, and also errors in time discipline.